Factors Influencing the Discordancy Between Intraoperative Frozen Sections and Final Paraffin Pathologies in Ovarian Tumors - Shen, Hung; Hsu, Heng-Cheng; Tai, Yi-Jou; Kuo, Kuan-Ting; Wu, Chia-Ying; Lai, Yen-Ling; Chiang, Ying-Cheng; Chen, Yu-Li; Cheng, Wen-Fang (Frontiers in Oncology, 2021)
Aim. To retrospectively investigate the pre-operative clinical factors and ultrasonographic features that influence the accuracy of the intraoperative frozen section (IFS) of ovarian tumors. Patients and methods. Women with ovarian tumors that underwent IFS in one tertiary medical center were recruited from January 2010 to December 2018. Demographic and clinical data of these women were retrieved from medical records in the hospital’s centralized database. Results. A total of 903 ovarian tumors were enrolled, including 237 (26.2%) benign, 150 (16.6%) borderline tumor, and 516 (57.2%) malignant. The overall accuracy of IFS among all specimens was 89.9%. The sensitivities of IFS in diagnosing borderline tumors (82.0%) and malignant tumors (88.2%) were lower than in diagnosing benign tumors (98.7%, p < 0.001, Z-test). The specificity of diagnosing malignant tumors (99.7%) was significantly higher than that of diagnosing benign tumors (94.7%, p < 0.001, Z-test). The group with discordant IFS and final paraffin pathology (FPP) had younger age (47.2 ± 14.0 vs. 51.5 ± 11.8 years, p = 0.013, Mann-Whitney U test), and higher percentage of early-stage disease (85.2% vs. 65.1%, p = 0.001, chi-square test) and mucinous (39.3% vs. 3.3%) and endometrioid histologic types (34.4% vs. 20.2%) than the concordant group (all by chi-square test). Menopause (OR 0.34, 95% CI 0.15–0.76, p = 0.009), multicystic tumor in ultrasound (OR 2.14, 95% CI 1.14–4.01, p = 0.018), and ascites existence (OR 0.33, 95% CI 0.14–0.82, p = 0.016) were factors related to the discordant IFS by multivariate analysis. Conclusions. IFS has good accuracy in the diagnosis of ovarian tumors. We recommend more frozen tissue sampling for sonographic multicystic tumors in premenopausal women to improve the accuracy of IFS.